Promiscuous enzymatic activity-aided multiple-pathway network design for metabolic flux rearrangement in hydroxytyrosol biosynthesis - Wei Chen (Nature Portfolio, 2019)
Metabolic engineering usually focuses on manipulating enzyme(s) within a single pathway. Here, the authors show that a promiscuous enzymatic activity-based multiple-pathway design can minimize cell metabolic burden and allow carbon flow rearrangement, leading to efficient hydroxytyrosol biosynthesis.